Morphological and molecular identification of two Florida populations of foliar nematodes (Aphelenchoides spp.) isolated from strawberry with notes on their phytoparasitic status - Oliveira, Clemen Junior de (2019)
Morphological and molecular analyses were conducted to determine the taxonomic status of two populations of foliar nematodes from a Florida strawberry field tentatively identified as putative Aphelenchoides besseyi and A. fujianensis. Both nematode species were reared in plates containing cultures of the fungus Monilinia fructicola. The morphological characters of the Florida population of putative A. besseyi fit those of the original description and other re-descriptions of this species. The population of putative A. fujianensis did not fit the morphology described in the original description from China because it was male-less and with females lacking a functional spermatheca, whereas A. fujianensis was described as an amphimictic species and with females having a large spermatheca. Phylogenetic relationships among the Florida populations and other reference populations of Aphelenchida are given as inferred from the analyses of the near full-length small subunit ribosomal RNA (SSU), partial large subunit ribosomal RNA (LSU) and partial mitochondrial cytochrome oxidase gene subunit I (COI) gene sequences. These phylogenetic analyses were conducted using reference sequences of other geographical distant populations of A. besseyi, a species described without molecular analysis, and A. fujanensis, including that from the original description of this species. The results of the molecular study suggest that the sequences of the population of putative A. besseyi from Florida strawberry and those of other reference populations of this species are not congruous. The lack of congruity among them indicates that A. besseyi is a species complex. The Florida strawberry population was originating from strawberry stolons imported from North Carolina (USA), the type locality of A. besseyi. The new sequences obtained for this population are the most representative of this species. Furthermore, the results of the phylogenetic analyses indicated that the sequences of the Florida population of the putative A. fujianensis do not match those of the type population of A. fujianensis validating the results of the morphological analysis. The sequences of the Florida population were congruous with those of some morphological similar populations from Brazil identified as A. fujianensis suggesting that the Florida and Brazilian populations are conspecific and are not A. fujanensis. Additional comparative studies of the Florida population with described Aphelenchoides species having the tail terminus with a mucro bearing hair-like processes will clarify its taxonomic status as a representative of another already described or an undescribed taxon in the group of Aphelenchoides species with stellate tail. In the phytoparasitic studies, the Florida population of putative A. besseyi from M. fructicola cultures infected strawberry and other selected plant species. Strawberry and gerbera daisy were the most suitable hosts compared to soybean. The population levels in strawberry were lower than those observed in gerbera daisy. The nematode behaved as an ectoparasite on strawberry without any evidence of endoparasitism. Ectoparasitism was observed also in gerbera daisy. Gerbera daisy is reported as a new host of A. besseyi. Very low population levels were observed in soybean indicating that this legume is not a good host of the Florida population of A. besseyi under the conditions of this experiment. Alfalfa was not infected by the nematode confirming the selective host preference of this Florida population of A. besseyi. The results of this study using the population of putative A. fujianensis at initial inoculum levels of 1000 specimens per plant clearly indicated that this species has mycetophagous habits. The population levels observed in the four crops mentioned above were low and did not exceed 34 specimens per plant (less than 2 specimens per gram of fresh tissues). On the contrary, inoculated and senescent soybean seedlings, kept in a greenhouse for 130 days, harbored high population levels to up 553 specimens per gram of desiccated tissues, when fungi infecting the decaying stem tissues became available as a food source. Although, this nematode population is mainly a mycetophagous species, it can behave as a phytoparasite under certain conditions as it was shown by the detection of nematode specimens inside the trichomes of soybean stem. Additionally, the localized inoculation of 300 nematodes applied with pieces of filter paper adhering to the blade of the soybean leaves resulted in nematode penetration and colonization of the mesophyll with subsequent development of foliar symptoms like those reported for other foliar nematodes.